Conflict resolution after the pandemic : building peace, pursuing justice - Rubenstein, Richard E.; Simmons, Solon (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"In this edited volume, experts on conflict resolution examine the impact of the crises triggered by the coronavirus and official responses to it. The pandemic has clearly exacerbated existing social and political conflicts, but, as the book argues, its longer-term effects open the door to both further conflict escalation and dramatic new opportunities for building peace. In a series of short essays combining social analysis with informed speculation, the contributors examine the impact of the coronavirus crisis on a wide variety of issues, including nationality, social class, race, gender, ethnicity, and religion. They conclude that the period of the pandemic may well constitute a historic turning point, since the overall impact of the crisis is to destabilize existing social and political systems. Not only does this systemic shakeup produce the possibility of more intense and violent conflicts, but also presents new opportunities for advancing the related causes of social justice and civic peace"--
Introduction / Richard E. Rubenstein and Solon Simmons -- Big peace : an agenda for peace and conflict studies after the coronavirus catastrophe / Solon Simmons -- Lessons from disaster : history and the current crisis / Peter N. Stearns and Richard E. Rubenstein -- From the frying pan to the fire : the next stage of environmental crisis and its implications conflict resolution / Michael Shank -- Pandemics, globalization and contentious politics / Agnieszka Paczynska and Terrence Lyons -- Global migration after the pandemic / Omar Grech -- COVID-19, nationalism, and changing political identities / Karina Korostelina -- Resolving great power conflicts in the post-pandemic era / Mohammed Cherkaoui -- Twilight of the market gods : the revaluation of socioeconomic values in a period of social reconstruction / Michael English -- The pandemic and the struggle for racial and ethnic justice in America / Arthur Romano -- The impact of crisis and recovery on gender relationships, roles, and conflict / Scheherazade Jafari -- Eternal and internal security : impact of the crisis on religious identity and peacemaking / Charles Davidson -- Peace engineering in a post-pandemic world / Alpasian Ozerdem and Lisa Schirch -- Threats of escalation and prospects for peace in Israel-Palestine / Oded Adomi Leshem -- The future of U.S.-China relations : the rocky road to peace / Gao Qing -- Concluding note / Richard E. Rubenstein and Solon Simmons.
OCLC-licensed vendor bibliographic record.
Keywords: Social conflict; Conflict management; Peace-building.; Social justice; COVID-19 Pandemic, 2020- -- Social aspects; POLITICAL SCIENCE -- Peace; POLITICAL SCIENCE -- Political Freedom & Security -- International Security; POLITICAL SCIENCE -- International Relations -- General